2013
DOI: 10.1558/cj.v16i3.407-424
|View full text |Cite
|
Sign up to set email alerts
|

Giving Help and Praise in a Reading Tutor with Imperfect Listening--Because Automated Speech Recognition Means Never Being Able to Say You're Certain

Abstract: Human tutors make use of a wide range of input and output modalities, such as speech, vision, gaze, and gesture. Computer tutors are typically limited to keyboard and mouse input. Project LISTEN's Reading Tutor uses speech recognition technology to listen to children read aloud and help them. Why should a computer tutor listen? A computer tutor that listens can give help and praise naturally and unobtrusively. We address the following questions: When and how should a computer tutor that listens help students? … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…LISTEN is one of these systems that provides various types of assistance when a child clicks for help or the system decides the child needs help. The feedback form provided on a word is randomly selected from the available options [10,4]. Research shows that the children's reading fluency and comprehension improved after practicing with the online tutor, compared to Sustainable Silent Reading (SSR) and regular classroom instruction [11,12].…”
Section: Research Backgroundmentioning
confidence: 99%
“…LISTEN is one of these systems that provides various types of assistance when a child clicks for help or the system decides the child needs help. The feedback form provided on a word is randomly selected from the available options [10,4]. Research shows that the children's reading fluency and comprehension improved after practicing with the online tutor, compared to Sustainable Silent Reading (SSR) and regular classroom instruction [11,12].…”
Section: Research Backgroundmentioning
confidence: 99%
“…Additionally, ASR plays a vital role in continuous learning and learning assessment by allowing users to practice pronunciation and conversation, providing immediate feedback on accuracy, and creating student models to evaluate learning proficiency and performance. Mostow et al identified three areas of knowledge necessary to support the ASR engine: the acoustic model, the pronunciation lexicon, and the language model [24].…”
Section: Modelsmentioning
confidence: 99%
“…• The feedback provided by the RT is subtle: It merely does not highlight incorrectly read text as the reader proceeds; further, it signals that the program is waiting for improved input only if there is a major delay or error; • Feedback provided by the RT is imperfect in the sense that its ASR technology does not catch every single reading error and stop to offer help (Mostow & Aist, 1999). Consequently, discourse flow is not frequently interrupted, thus helping to balance contending fluency and accuracy performance goals.…”
Section: Moderating Effect Of Good Quality Classroom Instruction With...mentioning
confidence: 99%